Faktor-Faktor yang Menyebabkan Penyakit Gastritis pada Pasien di Puskesmas Tanjung Beringin Kabupaten Pesisir Selatan dengan Menggunakan Analisis Faktor - setia ningsih m; dewi murni (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Gastritis or commonly referred as magh/ulcer is an inflammation that could result in swelling mucosa of ulcer and dyspepsia. Gastritis is one of the top ten diseases in Tanjung Beringin Health Center, Pesisir Selatan District and has an increase in the number of gastritris patients every year start from 2016 to 2018. This research was conducted with the purpose of knowing the cause of gastritis patients at the Tanjung Beringin Health Center, Pesisir Selatan District. In this research used primary data with shared some questionnaires to 88 people who suffer of gastritis in the Tanjung Beringin Health Center, Pesisir Selatan District. One of the statistical analyzes used in this research is factor analysis. Based on research result there two factors that being cause gastritis disease in patients at the Tanjung Beringin Health Center, Pesisir Selatan District 1) dietary habit, drinking caffeine/coffee habits and smoking 2) Age, drug habits and stress.Keywords–Gastritis, Dietary Habit, Factor Analysis.